MATHEMATICAL MODEL FOR THE ANALYTICAL USE OF BLOCKING CONTOUR IN GEARS WITH ASYMMETRIC TEETH - Hernández Ortega, Robert; Fernández Castañeda, Feliberto (Centro Azúcar Journal, 2016)
Blocking Contours are a graphical method. By means of this technique, the gear designer obtains the values of the correction coefficients, which meets the undercutting geometric constraints, contact ratio, interference and teeth pointing. This paper presents a mathematical model that allows non-interactive construction of blocking contour in the field of cylindrical external gears with asymmetric teeth. For this purpose, the equations defining the mentioned restrictions are modified and it is set the sequence in which they should be calculated. This makes possible the analytical use of the limits of blocking contour for establishing the dependence between the geometric parameters of these transmissions, thereby facilitating synthesis work.